Analysis and countering threats to the marketing position of the company in online communities - Пелещишин, Оксана Петрівна (Ukrainian Information Security Research Journal, 2013)
During use online communities in marketing should take into account possibility threats to the image and position of the company, the source of which can be as an online environment, and the activities of the company are. Traditional techniques of protection against aggressive actions require adaptation to the peculiarities of the communication environment of online communities. Tools for monitoring and analyzing the content of online communities to detect of attempts of information attacks from competitors or intruders are investigated in this work. The effective methods countering threats to position of the company in online communities are offered. Using online communities to propagate marketing information and interact with consumers is provided by the active participation of the company’s representatives in discussions. The community’s negative reaction for personnel’s unskilled activities may cause a threat to the image of the company. The article defines the requirements for marketers in online communities, the observance of which reduces the risk of compromising and improves the efficiency of propagation of marketing information. The mathematical model for optimal allocation of company’s representatives between sites of online communities is built which takes into account the efficiency of marketing communications and the importance of online communities to solve marketing problems.